Water, Electricity, and the Poor : Who Benefits from Utility Subsidies? - Komives, Kristin; Foster, Vivien; Halpern, Jonathan; Wodon, Quentin (Washington, DC: World Bank, 2012)
While consumer utility subsidies are widespread in both the water and electricity sectors, their effectiveness in reaching and distributing resources to the poor is the subject of much debate. This publication brings together empirical evidence on subsidy performance across a wide range of countries. It documents the prevalence of consumer subsidies, provides a typology of the many variants found in the developing world, and presents a number of indicators useful in assessing the degree to which such subsidies benefit the poor, focusing on three key concepts: beneficiary incidence, benefit incidence, and materiality. The findings on subsidy performance will be useful to policy makers, utility regulators, and sector practitioners who are contemplating introducing, eliminating, or modifying utility subsidies, and to those who view consumer utility subsidies as a social protection instrument.